An Analysis of Lexical Semantic Meaning in Album “Unorthodox Jukebox” by Bruno Mars - Gude, Adrianus; Talan, Alfridus; Suardana, Putu (UIBU, 2025)
Understanding the meaning of lyrics in contemporary popular music can be difficult because many expressions carry intentions that exceed their surface definitions. Responding to this issue, this study investigates how literal (lexical) meanings and context-based meanings operate in several tracks from Bruno Mars’ Unorthodox Jukebox album. The research adopts a qualitative descriptive approach in which the selected lyrics are examined through semantic classification, comparing dictionary-based meanings with the interpretive shifts that emerge from the surrounding lyrical environment. The analysis indicates that while numerous words retain straightforward lexical senses, their significance frequently expands when considered within the emotional and narrative structure of the songs. For example, in When I Was Your Man, the term man evolves from a simple reference to gender into an indicator of emotional development, regret, and accountability. Similarly, expressions such as heaven and locked out in Locked Out of Heaven evoke symbolic and affective layers not present in their literal meanings. Overall, the study highlights that a comprehensive interpretation of modern song lyrics requires attention to both lexical meaning and the contextual forces that reshape it.